Evaluation of the quality of groundwater used for irrigation in the Mina plain, Algeria - Gorine, Mohamed; Benkhelifa, Mohammed; Gacem, Farid; Bellague, Djamal (Revue des Sciences de l’Eau / Journal of Water Science, 2019)
The development of agriculture in the Mina plain is hampered by the drought that has occurred in recent years. As a result, water scarcity has favoured an intensive use of groundwater of poor quality. This behaviour is one of the forerunners of soil degradation. Knowing the quality of the irrigation water used becomes imperative. In this context, water samples from 178 wells in the Mina plain were subjected to a physico-chemical analysis, mainly electrical conductivity (EC), sodium adsorption ratio (SAR), and irrigation water quality index (IWQI), were used to identify water quality classes as well as residual alkalinity (RSC) to determine salinization pathways. The thematic maps established by the two methods (EC and SAR, IWQI) showed that 73.44% of the total area could be used for irrigation and that 87.55% of the total area may be used for irrigation in soils with high permeability where additional water should be applied to prevent salt accumulation. The residual alkalinity revealed two types of salinization: one neutral and one alkaline, representing respectively 149 and 29 wells. The electrical conductivity varied between 2.24 and 16.50 dS∙m-1, divided into two classes of salinity (C4, 44.03% and C5, 55.97%). SAR values fluctuated between a low of 4.28 and a high of 94.73, with S2 dominance accounting for 49.57% of the total area. IWQI’s assessment of groundwater quality revealed that 87.55% of the Mina study area is severely restricted, which is dominant in the southeastern and southwestern parts of the area. The remaining area, 12.44% or less, is in the high restriction category. This simple index uses the most important parameters that evaluate the quality of irrigation water for management.